Longer-term effectiveness of systemic family therapy compared with treatment as usual for young people after self-harm: An extended follow up of pragmatic randomised controlled trial. (January 2020) - Cottrell, D.J.; Wright-Hughes, A.; Eisler, I.; Fortune, S.; Green, J.; House, A.O.; Kerfoot, M.; Owens, D.W.; Simic, M.; McLellan, V.; Tubeuf, S.; Farrin, A.J.
Abstract: Background: Self-harm in adolescents is common and repetition frequent. Evidence for effective interventions to reduce self-harm is limited. Long term follow-up of existing studies is rare. Methods: Extended follow up, from 18 to at least 36-months, of the SHIFT trial: a pragmatic, multi-centre, individually-randomised, controlled trial involving young people (11–17) who had self-harmed at least twice and presented to Child & Adolescent Mental Health Services (CAMHS). SHIFT evaluated manualised family therapy (FT) versus treatment as usual (TAU) in reducing repetition of self-harm leading to hospital attendance 18 months post-randomisation. We obtained ONS mortality data, adult mental health data, and further details of hospital attendance from routine Hospital Episode Statistics (HES) data plus researcher follow-up. We assessed longer-term differences in outcome using multivariable Cox Proportional Hazards regression analysis, and assessed all-cause mortality and morbidity relating to hospital attendances for reasons other than self-harm. Study registration: ISRCTN 59793150 Outcomes: The original sample of 832 were randomised between April 2010 and December 2013. Extended follow-up continued until February 2017 for a median 55·4 months (range 0–82·5 months), providing post 18-month data for 804 (96·6%) participants, of whom 785 (94·4%) had a minimum of 36-months follow-up. There was no evidence of a between-group difference in the primary outcome during the extended follow-up period (Hazard Ratio (HR) 1·03; 95% CI: 0·83, 1·28; p-value=0·78), consistent with our findings in the original trial with 18 months follow-up (HR 1·14, 95% CI 0·87, 1·49; p-value 0·33). There was a reduced rate of self-harm in older participants aged 15–17 (HR 0·7, 95% CI 0·56, 0·88), as compared with those aged 11–14; and significantly increased rates of self-harm in participants whose index episode combined self-injury and poisoning (HR 1·8, 95% CI 1·2, 2·7). Two deaths were reported during the extended follow up period. Interpretation: For adolescents referred to CAMHS after self-harm, having self-harmed at least once before, trial FT confers no benefits over TAU in reducing subsequent hospitalisation for self-harm over 18 months or 36 months. Funding: NIHR HTA Reference: 07/33/01